Optimalisasi Pembelajaran melalui Bimbingan Belajar Gratis untuk Meningkatkan Kualitas Pendidikan di GKSI Sungai Maram - Isak P. Puling (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
This Student Creativity Program (PKM) aims to develop and optimize the learning guidance (bimbel) activities at GKSI Sungai Maram as a learning platform that focuses not only on improving academic performance but also on the development of character and Christian values in children. In this activity, students, as community service participants, actively play a role in teaching and mentoring students, ranging from elementary to middle school age. The implementation of this PKM is intended to help children enhance their academic understanding outside of school hours, introduce them to the moral teachings contained in the Bible, and strengthen their social skills. With support from the community and the management of GKSI Sungai Maram, this program is expected to have a positive impact on the students' development, both academically and spiritually.The expected outcomes of this program include the improvement of the quality of children's education, the formation of positive character traits, and the growth of awareness regarding the importance of holistic education, which emphasizes not only intellectual intelligence but also moral development and the relationship with God.